Nimbolide-based nanomedicine inhibits breast cancer stem-like cells by epigenetic reprogramming of DNMTs-SFRP1-Wnt/β-catenin signaling axis - Mohapatra, Priyanka; Madhulika, Swati; Behera, Somalisa; Singh, Priya; Sa, Pratikshya; Prasad, Punit; Swain, Rajeeb Kumar; Sahoo, Sanjeeb Kumar (Molecular therapy. Nucleic acids, 2023)
Triple-negative breast cancer (TNBC) harbors a high percentage of breast cancer stem-like cells (BCSCs) that significantly contribute to poor prognosis, metastasis, and relapse of the disease. Thus, targeting BCSCs could be a promising approach to combat TNBC. In this context, we investigated nimbolide (Nim), a limonoid triterpenoid that has potent anticancer properties, but poor pharmacokinetics and low bioavailability limit its therapeutic application. So, to enhance the therapeutic potential of Nim, Nim-encapsulated poly(lactic-co-glycolic acid) (PLGA) nanoparticles (Nim NPs) were formulated and the anticancer stem cell (CSC) effects evaluated in vitro and in vivo. In vitro studies suggested that Nim NPs significantly inhibited several inherent characteristics of BCSCs, such as stemness, self-renewability, chemoresistance, epithelial-to-mesenchymal transition (EMT), and migration in comparison to native Nim. Next, the mechanism behind the anti-CSC effect of Nim was explored. Mechanistically, we found that Nim epigenetically restores tumor suppressor gene secreted frizzled-related protein 1 (SFRP1) expression by downregulating DNA methyltransferases (DNMTs), leading to Wnt/β-catenin signaling inhibition. Further, in vivo results demonstrated that Nim NPs showed enhanced anti-tumor and anti-metastatic effects compared to native Nim in two preclinical models without any systemic toxicity. Overall, these findings provide proof of concept that Nim-based phytonanomedicine can inhibit BCSCs by epigenetic reprogramming of the DNMTs-SFRP1-Wnt/β-catenin signaling axis. [Display omitted] Sahoo and colleagues showed that Nimbolide-based phytonanomedicine exhibited enhanced anti-tumor activity by epigenetic reprogramming of DNMTs-SFRP1-Wnt/β-catenin signaling axis in breast cancer stem cells (BCSCs).